Estrategia metodológica para mejorar el proceso de evaluación de los aprendizajes y elevar el rendimiento académico e los estudiantes del octavo año de educación básica, en el área de Matemática del colegio técnico mixto “27 de Febrero” de la ciudad de Loja - Ruales Segarra, Mario Vicente (2015)
This research work relates to the topic: METHODOLOGICAL STRATEGY TO IMPROVE THE ASSESSMENT PROCESS OF LEARNING AND RAISE THE ACADEMIC PERFORMANCE IN THE STUDENTS OF EIGHT YEAR OF BASIC EDUCATION, IN THE MATHEMATICS AREA AT “27 DE FEBRERO HIGH SCHOOL” IN TH E LOJA CITY. It was developed according to the overall objective: To design a methodological strategy to improve the assessment process of learning, so it can raise the academic performance of students in eight year of General Basic Education, in the Mathematics Area, at “ 27 de Febrero ” High s chool of the Loja city. The main methods used were: the scientific method, Inductive – deductive, analytic-synthetic, deductive hypothetical, historical logic and the systems approach, that allows to study and analyze the theoretical and empirical data about the methodological strategy used by mathematics teachers to evaluate mathematical learning and its impact on the students’ academic performance; The techniques we used were: The survey and the questionnaire as a tool. To obtain basic information about the topic this study was realized to 10 teachers and 170 students of Eighth year of General Basic Education at “27 de Febrero” High school of the Loja city. The results we obtained are in complete agreement with the formulated hypothetical approach so, we are demonstrating the methodological strategy used by teachers to evaluate the mathematical learning contributes only a little to raise the academic performance of their students. It means, when the results were interpreted and, the hypothesis were contrasted it was determined all teachers of mathematics prioritize the summative evaluation. They evaluate by taking exams using instruments of the traditionalist pedagogy and the educational technology. They promote the unfair competition among students. Instead of this, they should create spaces for reflection and analyses such as group activities, where the best students help to guide the rest of the students with the purpose to generate significant learning and to obtain a satisfactory academic performance. Teachers use improperly the interrogation and the problems solving techniques. In this way, they are subject just to goals verification, mechanization of mathematical content and the behavior changes. According to results of this research work, it is proposed to design a methodological strategy to improve the evaluation process of learning and raise the academic performance in the students of Eight year of Basic Education in the Mathematics Area at “27 de Febrero” High school of the Loja city